p53-Dependent Senescence in Mesenchymal Stem Cells under Chronic Normoxia Is Potentiated by Low-Dose γ-Irradiation - Ines Höfig; Yashodhara Ingawale; Michael J. Atkinson; Heidi Hertlein; Peter J. Nelson; Michael Rosemann (Stem Cells International)
Mesenchymal stem cells (MSCs) are a source of adult multipotent cells important in tissue regeneration. Murine MSCs are known to proliferate poorly in vitro under normoxia. The aim of this study is to analyze the interaction of nonphysiological high oxygen and low-dose γ-irradiation onto growth, senescence, and DNA damage. Tri-potent bone marrow-derived MSCs from p53 wildtype and p53−/− mice were cultured under either 21% or 2% O2. Long-term observations revealed a decreasing ability of wildtype mMSCs to proliferate and form colonies under extended culture in normoxia. This was accompanied by increased senescence under normoxia but not associated with telomere shortening. After low-dose γ-irradiation, the normoxic wildtype cells further increased the level of senescence. The number of radiation-induced γH2AX DNA repair foci was higher in mMSCs kept under normoxia but not in p53−/− cells. P53-deficient MSCs additionally showed higher clonogeneity, lower senescence levels, and fewer γH2AX repair foci per cell as compared to their p53 wildtype counterparts irrespective of oxygen levels. These results reveal that oxygen levels together with γ-irradiation and p53 status are interconnected factors modulating growth capacity of BM MSCs in long-term culture. These efforts help to better understand and optimize handling of MSCs prior to their therapeutic use.